To the Calculation of the Average Value of the Volume Fraction of the Key Bulk Component at the Intermediate Stage of Mixing With an Inclined Bump - Kapranova, Anna; Verloka, Ivan; Bahaeva, Daria; Tarshis, Mikhail; Cherpitsky, Sergey (Frontiers in Energy Research, 2020)
The calculation of the increment angles of reflection of rarefied flows is proposed. The distribution functions over the states of macrosystems, which are constructed within the framework of the energy method, are taken into account. The basis is the results of stochastic modeling of mixing of flowing media with brushes. The effectiveness of the intermediate stage of mixing with the bump is analyzed.